When Peace is Personalized: The Clash between the BoP Charter and Indonesia’s Free and Active Foreign Policy - Natamiharja, Rudi; Kurniawan, Robi Cahyadi; Kpanya, Ovide Egide Manzanga; Ablin, Rainnade Geojona (Faculty of Law, Universitas Jambi, 2026)
Background: This article critically examines the legal and constitutional implications of Indonesia’s engagement with the